Munchausen Syndrome Presenting with Bleeding per Nose, Ears, Eyes and Mouth1 (Journal of Armed Forces Medical College, Bangladesh, 2020)
In 1951, Richard Alan John Asher first reported Munchausen syndrome as a factitious disorder. The essential feature of this disorder is that patients feign physical symptoms to get admission in a hospital. These patients may feign symptoms of disorder of any organ system. Even experienced clinicians are deceived by these symptoms and histories presented by these patients. Usually they know which of the symptoms and diagnoses usually require hospital admission or medication. Because of rarity of this disease and lack of knowledge and awareness even among the physicians, often misdiagnosis occur which results in unnecessary use of medical tests and evaluations. For these reasons this is one of the toughest and challenging diagnoses in any medical set up. We present this rare case of a patient who presented to the department of emergency, ENT and Eye repeatedly with Bleeding per nose, ears, eyes and mouth for 8 months. The patient was successfully treated, initially with psychotropic then psychotherapy with no recurrence. This interesting and rare case is presented to create awareness amongst all specially to medical population about Munchausen syndrome so that they can be diagnosed easily and treated with efficiency as well as misdiagnosis and unnecessary use of medical resources can be avoided.JAFMC Bangladesh. Vol 15, No 2 (December) 2019: 237-239